Reduction of Phosphorus Using Electric Arc Furnace Slag Filters in the Macatawa Watershed (Michigan) - Steinman, Alan D.; Hassett, Michael; Oudsema, Maggie; Penn, Chad J. (Frontiers in Environmental Science, 2022)
Eutrophication is a major problem in lakes and rivers throughout the world. One such system is Lake Macatawa, located in West Michigan, which hydrologically connects to Lake Michigan. Lake Macatawa and its watershed suffer from excess phosphorus and sediment loads. The TMDL (total maximum daily load) for the lake calls for a total phosphorus (TP) reduction of 75%, which would reduce the water column TP concentration from 125 µg/L to 50 µg/L. Understanding how P moves through this landscape, into Lake Macatawa, and ultimately to Lake Michigan and the St. Lawrence Seaway, is critical to managing and controlling P runoff. A potentially significant source of P to Lake Macatawa occurs through agricultural tile drainage. Various best management practices (BMPs) have been implemented in the Macatawa watershed to reduce P loading, especially surface runoff, but their overall effectiveness has been limited. Iron slag, a waste product from the steel industry, can chemically bind P and has been used previously in agricultural settings. Three iron slag filters were installed at the end of agricultural tile lines in the Macatawa watershed and evaluated to assess their effectiveness in removing P, while also monitoring for the presence of potentially toxic chemicals leaching from the slag. After one year of slag filter performance, both SRP (soluble reactive phosphorus) and TP decreased in the tile drain effluent: percent reductions of SRP and TP ranged from 7.4% to 57.3% and 59.5% to 76.5%, respectively. Absolute concentrations of TP were reduced to between 100 and 329 µg/L, which still exceeds the 50 µg/L goal for Lake Macatawa. Concentrations of toxic metals, PAH (polycyclic aromatic hydrocarbons) compounds, and cyanide all were at levels below drinking water standards. Our preliminary conclusions are that the installation of these filters should be targeted to areas where tile drain effluent P levels are very high (SRP > 250 µg/L) to obtain an optimal cost/benefit ratio. While they are not a panacea, when installed in combination with other BMPs (Best Management Practices), iron slag filters may play an important localized role in reducing P to Lake Macatawa and farther downstream.